PROFIL BERPIKIR KRITIS SISWA SMAS KATOLIK LAMAHOLOT WITIHAMA DALAM PEMBELAJARAN SEJARAH BERBASIS LITERASI DIGITAL (Study kasus di smas katolik lamaholot kecamatan witihama NTT) - yohanes dewanto lama; Muhammad Naharuddin Arsyad (Jurnal Ilmiah Wahana Pendidikan, 2023)
The background of this research is to see that Critical Thinking in the Literacy era is needed or must be owned by a student to be able to compete in the midst of globalization and modernization. However, there is no research that examines students' critical thinking, specifically for students of the Lamaholot Private Senior High School, Witihama Catholic High School. So the fear is that, don't let the nation's successors, especially in history lessons which record flashbacks of life from ancient times to present times, forget the importance of the critical thinking profile that educators don't have. Because, the pattern of critical thinking is one of the ways of thinking that is carried out in developing history lessons and also developing the mindset of students at SMAS Lamaholot Witihama Catholic School. The purpose of this study was to determine the development of a digital literacy-based history learning process at Lamaholot Witihama Catholic High School and to find out students' critical thinking processes in learning history as a basis for developing digital literacy-based learning methods using the YouTube application to improve critical thinking for history learning. The results of this research are expected to provide awareness to the nation's next generation to always apply and develop critical thinking profiles especially for the development of history learning based on digital literacy. Because, the profile of critical thinking in history lessons in the era of digital literacy opens insights to be able to develop and compete in an ideal way of thinking. This study uses a descriptive qualitative research method by analyzing interviews conducted with informants or informants. This research will be conducted in Adonara, East Flores Regency, East Nusa Tenggara province. Informants or resource persons in this study were teachers and students at SMAS Catholic Lamaholot.